Regional Differences in Hospital Costs of Acute Ischemic Stroke in China: Analysis of Data From the Chinese Acute Ischemic Stroke Treatment Outcome Registry - Lu, Yuxuan; Sun, Weiping; Shen, Zhiyuan; Sun, Wei; Liu, Ran; Li, Fan; Shu, Junlong; Tai, Liwen; Li, Guozhong; Chen, Huisheng; Zhang, Guiru; Zhang, Lei; et al. (Frontiers in Public Health, 2021)
Background and purpose: Studies on the regional differences in hospital costs of acute ischemic stroke (AIS) are scarce in China. We aimed to explore the regional differences in hospital costs and identify the determinants of hospital costs in each region. Methods: Data were collected from the Chinese Acute Ischemic Stroke Treatment Outcome Registry (CASTOR), a multicenter prospective study on patients diagnosed with AIS and hospitalized from 2015 to 2017. Univariable and multivariable analyses were undertaken to identify the determinants of hospital costs of AIS. Results: A total of 8547 patients were included in the study, of whom 3700 were from the eastern area, 2534 were from the northeastern area, 1819 were from the central area, and 494 were from the western area. The median hospital costs presented a significant difference among each region, which were 2175.9 dollars, 2175.1 dollars, 2477.7 dollars and 2282.4 dollars in each area, respectively. Each region showed a similar hospital cost proportion size order of cost components, which was Western medicine costs, other costs, diagnostic costs, and traditional medicine costs, in descending order. Male sex, diabetes mellitus, severe stroke symptoms, longer length of stay, admission to the intensive care unit, in-hospital complications of hemorrhage and thrombectomy were independently associated with hospital costs in most regions. Conclusion: The hospital costs in different regions showed a similar proportion size order of components in China. Each region had different determinants of hospital costs, reflecting the current medical conditions and providing aspects to increase medicine efficiency according to each region’s situation.